Psychometric Properties of the Emotional Skills and Competence Questionnaire for Teachers - Valente, Sabina (2023)
The Emotional Skills and Competence Questionnaire, as an emotional intelligence self-report measure, is based on the theoretical framework of the Mayer-Salovey emotional intelligence model and presents good psychometric properties in a crosscultural setting. Different studies showed that emotional intelligence has a positive impact on teachers’ work. So, the present study aimed to analyze the psychometric proprieties of the Emotional Skills and Competence Questionnaire adapted for teachers. A sample of 843 teachers from Portuguese schools (1st to 12th grades) was used. The scale was back-translated, adapt and participants completed a battery of questionnaires: The Emotional Skills and Competence Questionnaire for Teachers (ESCQ-T), and the Teacher Sense of Efficacy Scale. Statistical analysis included structural equation modeling, and results showed a good fit with the original factor structure, a robust reliability coefficient, and good psychometric validity for ESCQ-T. Also, relationships with teacher efficacy were found. So, the results suggested that it is a valid measure for assessing teachers’ emotional skills and emotional competence. In conclusion, the ESCQ-T demonstrated adequate psychometric properties and can be used to assess teachers’ emotional skills and emotional competence.